2019
DOI: 10.1016/j.bbabio.2018.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of B800 bacteriochlorophyll binding site specificity in the Rhodobacter sphaeroides LH2 antenna

Abstract: The light-harvesting 2 complex (LH2) of the purple phototrophic bacterium Rhodobacter sphaeroides is a highly efficient, light-harvesting antenna that allows growth under a wide-range of light intensities. In order to expand the spectral range of this antenna complex, we first used a series of competition assays to measure the capacity of the non-native pigments 3-acetyl chlorophyll (Chl) a , Chl d , Chl f or bacterioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 84 publications
(143 reference statements)
4
46
0
Order By: Relevance
“…It is noticeable that k ET800 for Sphe S 1 → BChl b Q y is an apparent outlier from the overall trend. Our past studies demonstrated that this pigment correctly binds within the B800 site (Swainsbury et al 2019) so this result is rather surprising. However, in Fig.…”
Section: Estimate Of S 1 State Energy For Lh2-bound Spheroidenementioning
confidence: 93%
See 4 more Smart Citations
“…It is noticeable that k ET800 for Sphe S 1 → BChl b Q y is an apparent outlier from the overall trend. Our past studies demonstrated that this pigment correctly binds within the B800 site (Swainsbury et al 2019) so this result is rather surprising. However, in Fig.…”
Section: Estimate Of S 1 State Energy For Lh2-bound Spheroidenementioning
confidence: 93%
“…sphaeroides cells lacking the CrtA gene [reported previously in (Chi et al 2014)] were grown under 30 μmol photons s −1 m −2 illumination from OSRAM classic 116 W halogen bulbs in M22+ medium (Hunter and Turner 1988) supplemented with 0.1% w/v casamino acids. B800-B850 LH2 was purified by ion-exchange chromatography followed by size-exclusion as previously described (Swainsbury et al 2019). To generate a set of LH2 complexes with alternative (B)Chls bound to the B800 site, purified LH2 was exchanged into pH 5.0 buffer containing lithium dodecyl sulfate (LDS).…”
Section: Bacterial Growth and Lh2 Purification And Reconstitution Witmentioning
confidence: 99%
See 3 more Smart Citations